2008
DOI: 10.1007/978-3-540-88564-1_6
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Comparison of RDF Data Management Approaches in a SPARQL Benchmark Scenario

Abstract: Abstract. Efficient RDF data management is one of the cornerstones in realizing the Semantic Web vision. In the past, different RDF storage strategies have been proposed, ranging from simple triple stores to more advanced techniques like clustering or vertical partitioning on the predicates. We present an experimental comparison of existing storage strategies on top of the SP 2 Bench SPARQL performance benchmark suite and put the results into context by comparing them to a purely relational model of the benchm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 9 publications
0
52
0
4
Order By: Relevance
“…In 2009, Schmidt et al compared Sesame triplestore with the triple table, vertical partitioned storage scheme and the native relational scheme on MonetDB, a column-store relational database. This study concluded that none of the RDF schemes was competitive to the native relational scheme [39]. In 2010, MahmoudiNasab and Sakr also compared the triple table, property table and vertical partitioned storage scheme with the native relational scheme on IBM DB2.…”
Section: Related Workmentioning
confidence: 99%
“…In 2009, Schmidt et al compared Sesame triplestore with the triple table, vertical partitioned storage scheme and the native relational scheme on MonetDB, a column-store relational database. This study concluded that none of the RDF schemes was competitive to the native relational scheme [39]. In 2010, MahmoudiNasab and Sakr also compared the triple table, property table and vertical partitioned storage scheme with the native relational scheme on IBM DB2.…”
Section: Related Workmentioning
confidence: 99%
“…In this situation, all vertical partitions need to be accessed and unioned together or merged: this class of queries is also problematic for property tables; however, since there are fewer total property tables than vertical partitions, the relative performance overhead of unioning or merging everything together is more significant for the vertical partitioning approach. Although queries that do not restrict on property value are common in synthetic SPARQL benchmarks [42], we have found that, in practice, for the RDF applications we have worked with, such queries are rare. However, should an application contain queries that do not restrict on property value, the vertical partitions can be supplemented with auxiliary data structures that store data in a way that can accelerate this class of queries.…”
Section: Fewer Unions (Relative To the Property-class Schema Approach)mentioning
confidence: 99%
“…Executing path queries on very large RDF data sets like social network graphs with billions of entries is a non-trivial task that typically requires many resources and computational power [1,8,9,21,30]. RDFPath is a declarative RDF path query language, inspired by XPath and designed especially with regard to the MapReduce model.…”
Section: Rdfpathmentioning
confidence: 99%
“…However, management of large RDF graphs is a non-trivial task and single machine approaches are often challenged with processing queries on such graphs [30]. One solution is to use high performance clusters or to develop custom distributed systems that are commonly not very cost-efficient and also do not scale with respect to additional hardware [1,8,9].…”
Section: Introductionmentioning
confidence: 99%